PENGARUH LAMA PERENDAMAN DALAM ZPT HORMAX TERHADAP PERTUMBUHAN UBI BANGGAI (Dioscorea spp) - Hasrawati; Djamaluddin, Ismail; Pelia, Lani (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Banggai Banggai Yam which has a fairly high carbohydrate content can be used as an alternative food source. Therefore, this plant can be developed as one of the superior commodities for additional food besides rice. The most fundamental problem with Banggai Yam t this time is that Banggai Yam an only be cultivated once a year. so researchers tried to conduct research using hormones or plant growth regulators (PGRs) in plants to support the process of accelerating the growth of Banggai Yam  lants. The level of PGR absorption by plants is also determined by the duration of soaking the cuttings. For this reason, this study aims to determine the effect of the duration of tuber soaking on the growth of Banggai Yam. This study used a Randomized Block Design (RAK) with 4 treatments of PGR Hormax (W) soaking time with a concentration of 6 mL/L of water consisting of W0 (control), W1 (20 minutes/6mL/L of water), W2 (40 minutes/6mL/L of water), W3 (60 minutes/6mL/L of water). Each treatment was repeated 6 times. The results were analysed using ANOVA using package ‘stats’ and displayed in diagram form using package ‘ggplot2’. Data were analysed using RStudio 2023.12.0 software. The results showed that the W2 treatment (40 minutes/6mL/L water) gave a real effect on the sprouting speed of Banggai yam plants. The results of this study, can be used for cultivators of Banggai Yam, because with these results it will be able to help them to increase the speed of sprouting of Banggai Yam plants.